Ethical Issues in Marketing Communication for Real Estate in India - Sen, Dhruba Jyoti (International Review of Management and Marketing, 2021)
The goal of this paper is to put forth the ethical challenges in the field of marketing communication in Indian real estate industry. It is necessary to understand the concept of ethics which the organization and the managers adopt. This paper explores the existing studies and reports to understand the ethical norms and values for marketing communication. The existing codes and regulations applicable for the real estate industry are discussed to the extent it has relation with the marketing communication. Further, this paper endeavors to analyze the reasons behind the marketers getting engaged in unethical practices and to finally recommend how the organizations can address those issues. Keywords: Ethics, Real Estate, Marketing, Management, Business, Codes. JEL Classifications: A130, K250, M310, M370 DOI: https://doi.org/10.32479/irmm.11291